2012
DOI: 10.1164/rccm.201109-1706oc
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible Factor 1 Mediates Nasal Polypogenesis by Inducing Epithelial-to-Mesenchymal Transition

Abstract: hNECs undergo EMT during hypoxia and this process is critically mediated by HIF-1α and pSmad3. This study shows that hypoxia-induced EMT is likely to contribute to nasal polyposis in CRS, and suggests that HIF-1α be viewed as a therapeutic target for nasal polyposis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 47 publications
10
123
0
1
Order By: Relevance
“…S1A). We obtained similar results using human lung alveolar A549 cells, which undergo EMT upon exposure to TGF-b (Haynes et al, 2011) and hypoxia (Shin et al, 2012). Although EMT of A549 cells upon hypoxia took 7 days, as indicated by increased fibronectin and actin stress fibers, the fibronectin fibrils seen with TGF-b were mostly absent (supplementary material Fig.…”
Section: Resultssupporting
confidence: 65%
“…S1A). We obtained similar results using human lung alveolar A549 cells, which undergo EMT upon exposure to TGF-b (Haynes et al, 2011) and hypoxia (Shin et al, 2012). Although EMT of A549 cells upon hypoxia took 7 days, as indicated by increased fibronectin and actin stress fibers, the fibronectin fibrils seen with TGF-b were mostly absent (supplementary material Fig.…”
Section: Resultssupporting
confidence: 65%
“…Abnormalities that affect epithelial cilia function may also result in impaired mucociliary clearance. 28 31 either of which can lead to decreased mucociliary clearance. In fact, there is evidence that these near-anaerobic conditions may significantly contribute to the pathogenesis of CRS.…”
Section: Mucociliary Clearance: Mopping Away Bugs and Debrismentioning
confidence: 99%
“…In addition, PC1/3 cells display downregulation of epithelial markers and upregulation of mesenchymal markers, referred to as EMT [2,4]. Recently, SHIN et al [8] showed hypoxia-induced EMT via a SMAD3-dependent mechanism in cultured human nasal epithelial cells and in epithelial cells lining nasal polyps, suggesting an important role for EMT in the pathogenesis of nasal polyps. Our proteomic analysis shows that differentially produced proteins between PC1/3 cells and mock cells are implicated in carbohydrate metabolism, cell proliferation, cytoskeletal reorganisation, DNA metabolism and signal transduction (online supplementary figure S1 and table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression levels of N-cadherin, snail and twist were significantly higher in cytomix-treated NHNE cells compared to TGF-b1-treated cells. Moreover, PC1/ 3 expression was induced by cytomix, but not by TGF-b1, indicating the involvement of PC1/3 in cytomixmediated EMT, but not in TGF-b1-induced EMT; TGF-b1 signalling was examined by measuring the levels of phospho-SMAD3 (p-SMAD3) [8]. We further examined the relationships between PC1/3 and EMT markers in nasal polyps and found that PC1/3 expression was positively correlated with loss of E-cadherin…”
Section: Pc1/3 Expression Is Positively Correlated With Emt Both In mentioning
confidence: 99%
See 1 more Smart Citation